1956
DOI: 10.1084/jem.104.3.411
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Enteric Shigella and Vibrio Infections in Mice and Guinea Pigs

Abstract: A method has been devised for inhibiting the normal enteric flora, permitting long term asymptomatic enteric infections of mice and guinea pigs with streptomycin-resistant strains of Shigella flexneri or Vibrio cholerae. Introduction of a streptomycin-resistant strain of E. coli into the intestinal tract of experimental animals resulted in a rapid elimination of the enteric pathogens studied. No in vitro production of antibiotic substances by this coli strain could be demonstrated. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
89
0

Year Published

1962
1962
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(95 citation statements)
references
References 10 publications
3
89
0
Order By: Relevance
“…It has been extensively documented in invertebrate-as well as vertebrate-associated commensal microbial communities (Veivers et al, 1982;Guarner and Malagelada, 2003;Dillon et al, 2005). The notion that colonization resistance could be a crucial component of host defense against pathogens and may be manipulated to the host's advantage makes it the subject of constant investigation for the past few decades (Freter, 1956;Lloyd et al, 1977;Van der Waaij and Van der Waaij, 1990;Rolfe, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…It has been extensively documented in invertebrate-as well as vertebrate-associated commensal microbial communities (Veivers et al, 1982;Guarner and Malagelada, 2003;Dillon et al, 2005). The notion that colonization resistance could be a crucial component of host defense against pathogens and may be manipulated to the host's advantage makes it the subject of constant investigation for the past few decades (Freter, 1956;Lloyd et al, 1977;Van der Waaij and Van der Waaij, 1990;Rolfe, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…No indication was given of the sites of implantation in the intestinal tract but streptomycin-resistant Salmonella were frequently cultured from the heart, blood and spleen. Freter (1956) established experimental shigellosis in mice but could find no gross symptoms on autopsy. produced a chronic infection in mice with Shigella dysenteriae 2 and obtained macroscopic and histological evidence of pathological damage.…”
Section: Discussionmentioning
confidence: 99%
“…Both Freter (1956) and observed that the presence in the gut of streptomycin-resistant E. coli caused the elimination of Shigella from faeces and Freter (1956) could not attribute this overgrowth to antibiotic action. The nature ofthe successful coliform colonization is not yet elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…The potent resistance of the gastrointestinal ecosystem of conventional rodents to colonisation with human enteric pathogens such as Shigella¯exneri or Vibrio cholerae has been known for many years [1]. In contrast, the resident digestive microbiota of the major proportion of the human population is not so ef®cient.…”
Section: Introductionmentioning
confidence: 99%